Protection of canola (Brassica napus) against fungal pathogens by strains of biocontrol rhizobacteria - Simonetti, Ester (2012)
Strains of Pseudomonas fluorescens and Bacillus amyloliquefaciens, isolated from soybean rhizosphere, inhibited mycelial growth of Botrytis cinerea and Sclerotinia sclerotiorum, in vitro. Leaves from Brassica napus seedlings, pre-inoculated with either of these bacteria, exhibited systemic protection against fungal pathogens. © 2012 Taylor and Francis Group, LLC.